Political Connection and the Readability of the MD&A Disclosure - Iman Harymawan; Tubagus Algan Roiston (AKRUAL: JURNAL AKUNTANSI, 2022)
This research examined the relationship between politically connected companies and the readability of the company's MD&A. Our results show that in the Indonesian setting, the experience of parliamentarians (DPR, MPR), regional heads and local government officials at the company executive level plays an important role in the readability of a company's Management Discussion & Analysis (MD&A). Based on self-presentation theory, we suspect that companies with political connections make it possible to make the disclosures on the company's MD&A easy to read because the management with political connections puts forward their image in the stakeholders' eyes. The narrative that is conveyed is easier to understand as a result. Besides this, management who come from the political circle have the talent and expertise of managing their image in the public eye, thus enabling the management to convey the narrative on MD&A in a way that is easy to read for reasons of concealing the company performance or maintaining their image. We also tested the endogeneity effect using Coarsened Exact Matching Regression (CEM) to confirm our findings and obtained the same result as our previous assumption - that politically connected companies have an MD&A that is easy to read.